Reply to: Can wolves suppress goodwill for leopards? Need for further evidence - Farhadinia, M; Johnson, P; Hunter, L; Macdonald, D (Elsevier, 2018)
In our recent paper (Farhadinia et al. 2017) we reported some observations concerning 23 attitudes to large predators in northeaster Iran. One of our findings was that attitudes to 24 leopards were more negative among respondents reporting more stock loss to wolves. We 25 speculated that measures to reduce conflict with wolves might therefore be beneficial for 26 leopard conservation. Ghasemi and Kyle (2017) argue that our interpretation is spurious, and 27 that our approach provides a ‘poor foundation for future research’.